Not all visual symmetry is equal: Partially distinct neural bases for vertical and horizontal symmetry. (September 2017) - Cattaneo, Zaira; Bona, Silvia; Silvanto, Juha
Abstract: Visual mirror symmetry plays an important role in visual perception in both human and animal vision; its importance is reflected in the fact that it can be extracted automatically during early stages of visual processing. However, how this extraction is implemented at the cortical level remains an open question. Given the importance of symmetry in visual perception, one possibility is that there is a network which extracts all types of symmetry irrespective of axis of orientation; alternatively, symmetry along different axes might be encoded by different brain regions, implying that there is no single neural mechanism for symmetry processing. Here we used fMRI-guided transcranial magnetic stimulation (TMS) to compare the neural basis of the two main types of symmetry found in the natural world, vertical and horizontal symmetry. TMS was applied over either right Lateral Occipital Cortex (LO), right Occipital Face Area (OFA) or Vertex while participants were asked to detect symmetry in low-level dot configurations. Whereas detection of vertical symmetry was impaired by TMS over both LO and OFA, detection of horizontal symmetry was delayed by stimulation of LO only. Thus, different types of visual symmetry rely on partially distinct cortical networks. Highlights: We investigated whether vertical and horizontal symmetry shares common neural basis. fMRI-guided TMS was applied over either rLO, rOFA or Vertex. TMS over rLO impaired detection of vertically and horizontally symmetric targets. TMS over rOFA affected only vertical symmetry. The two symmetry orientations recruit partially different neural networks.